The comparative characteristics of snake and kiwi fruits - Gorinstein, Shela; Haruenkit, Ratiporn; Poovarodom, Sumitra; Park, Yong Seo; Vearasilp, Suchada; Suhaj, Milan; Ham, Kyung Sik; Heo, Buk Gu; Cho, Ja Yong; Jang, Hong Gi (My University, 2009)
In the time of globalization many of the tropical fruits can be find at the markets of Europe and North America. Most customers are not familiar with the nutritional and proliferative values of these fruits. Therefore, a less known snake fruit was compared with better known kiwi fruit, using fluorometry, FT-IR spectroscopy, several radical scavenging and proliferative assays and statistical evaluation. It was found similarity between snake fruit (cultivar Sumalee) and kiwi fruit (cultivar Hayward) in the contents of polyphenols (8.15-7.91, mg GAE g-1 DW), antioxidant values by DPPH (11.28-10.24, μMTE g-1 DW), and antiproliferative activities on both human cancer cell lines (Calu-6 for human pulmonary carcinoma, and SMU-601 for human gastric carcinoma, 90.5-87.6 and 89.3-87.1%, cell survival, respectively). In conclusion, snake fruit cultivar Sumalee is comparable with kiwi fruit cultivar Hayward. Two fruits can be used as supplements to the normal diet. Consumption of a combination of both fruits could be recommended in order to receive the best results. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Antioxidant potential; Antiproliferative activities; Bioactive compounds; Snake and kiwi fruits